2D MXene Nanomaterials: Insights into the Photothermal Conversion of 2D MXene Nanomaterials: Synthesis, Mechanism, and Applications (Adv. Funct. Mater. 47/2020). (18th November 2020) - Xu, Dingxin; Li, Zhidong; Li, Laisheng; Wang, Jing
Abstract : In article number 2000712, Laisheng Li, Jing Wang, and co‐workers discuss 2D MXenes, which demonstrate a superior photothermal conversion property by virtue of their electromagnetic wave absorption capacity and localized surface plasmon resonance effect. This efficient way to utilize solar energy that allows the transformation of solar illumination into thermal energy enables MXene‐based materials to be applied in diverse fields, such as solar steam generation and biomedicals.